Thyroid Laboratory Testing and Management in Women on Thyroid Replacement Before Pregnancy and Associated Pregnancy Outcomes - Lemieux, Patricia; Yamamoto, Jennifer M; Nerenberg, Kara A; Metcalfe, Amy; Chin, Alex; Khurana, Rshmi; Donovan, Lois Elizabeth (Thyroid (New York, N.Y.), 2021)
Women with hypothyroidism before pregnancy often require an increase in their levothyroxine dosage to maintain a euthyroid state during pregnancy. The objectives of this study were to investigate: (i) the frequency and distribution of thyrotropin (TSH) testing and levothyroxine dosage adjustment by gestational age, (ii) the magnitude of levothyroxine increase by the underlying etiology of hypothyroidism, and (iii) the relationship of overtreatment or undertreatment during pregnancy with adverse pregnancy outcomes among women using thyroid replacement before pregnancy. A retrospective cohort study of pregnancies in women on thyroid replacement before pregnancy in Alberta, Canada, was performed. Women using thyroid replacement anytime during the two years before pregnancy who delivered between October 2014 and September 2017 were included. Delivery records, physician billing, and laboratory and pharmacy administrative data were linked. Outcomes included characteristics of TSH testing, levothyroxine dosing, and pregnancy outcomes. The frequency and gestational timing of TSH testing and levothyroxine adjustments were calculated. Multiple logistic regression was used to test whether pregnancies with TSH <0.10 mIU/L (overtreatment) or TSH ≥10.00 mIU/L (undertreatment) compared with control pregnancies (TSH 0.10-4.00 mIU/L) were associated with adverse pregnancy and neonatal outcomes. Of the 10,680 deliveries, 8774 (82.2%) underwent TSH testing at least once during pregnancy, at a median gestational age of six weeks. An adjustment of levothyroxine dosage was made for 4321 (43.7%) during pregnancy. TSH in pregnancy below 0.10 mIU/L increased the odds of preterm delivery when compared with control pregnancies (adjusted odds ratio, 2.14 [95% confidence interval 1.51-2.78]). TSH ≥10.00 mIU/L during pregnancy was not associated with any adverse pregnancy or neonatal outcomes in the multivariable analysis. Although most women on thyroid replacement before conception had TSH measured at some point during pregnancy, it is concerning that 17.8% did not. Levothyroxine overtreatment in pregnancy was associated with preterm delivery. These findings suggest that clinicians should be careful to avoid overtreatment with levothyroxine in pregnancy.